2009
DOI: 10.1179/jmt.2009.17.1.14e
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Muscle Energy Technique on Pain in Individuals with Non-Specific Lumbopelvic Pain: A Pilot Study

Abstract: Muscle energy technique (MET) is a common conservative treatment for pathology around the spine, particularly lumbopelvic pain (LPP). MET is considered a gentle manual therapy for restricted motion of the spine and extremities 1 and is an active technique where the patient, not the clinician, controls the corrective force 2 . This treatment requires the patient to perform voluntary muscle contractions of varying intensity, in a precise direction, while the clinician applies a counterforce not allowing movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 17 publications
12
59
0
Order By: Relevance
“…The study revealed that the treatment group that received HVLA thrust manipulation had significant improvements in all variables while there was no change in the control group that received placebo intervention except for spinal mobility in flexion. Selkow et al [17] also supported our results where they examined the short term effect of MET on 20 patients with non-specific lumbopelvic pain, they reported that subjects who received MET demonstrated a significant decrease in VAS worst pain 24 hours after treatment while there was an increase in worst pain in the control group which received sham treatment. However, the technique used in the later study was different from that of our study.…”
Section: Discussionsupporting
confidence: 76%
“…The study revealed that the treatment group that received HVLA thrust manipulation had significant improvements in all variables while there was no change in the control group that received placebo intervention except for spinal mobility in flexion. Selkow et al [17] also supported our results where they examined the short term effect of MET on 20 patients with non-specific lumbopelvic pain, they reported that subjects who received MET demonstrated a significant decrease in VAS worst pain 24 hours after treatment while there was an increase in worst pain in the control group which received sham treatment. However, the technique used in the later study was different from that of our study.…”
Section: Discussionsupporting
confidence: 76%
“…Further research can be done with large sample size and follow up of the patients can be implemented in order to see the long-term effect of MET post study. [11]. Patil Prachi et al also concluded the efficacy of MET in reducing disability.…”
Section: Resultsmentioning
confidence: 99%
“…The subject was asked to "push their leg into the therapist's shoulder" and "push up with the opposite leg into therapist's hand. A total of 5 contractions were resisted by a force equal to the subject's, held for 5 seconds with 5 seconds rest between each contraction [14].…”
Section: Treatmentmentioning
confidence: 99%
“…Lastly, MET is a low-force isometric contraction in a pain-free position. In conclusion, this technique is not painful or harmful to the patient [14]. The therapist provides resistive force counter to push patients' muscle contraction, aimed to help in restoring musculoskeletal functions [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation